Nitrogen-Doped Carbon Dots as A New Substrate for Sensitive Glucose Determination - Hanxu Ji; Feng Zhou; Jiangjiang Gu; Chen Shu; Kai Xi; Xudong Jia (Sensors, 2016)
Nitrogen-doped carbon dots are introduced as a novel substrate suitable for enzyme immobilization in electrochemical detection metods. Nitrogen-doped carbon dots are easily synthesised from polyacrylamide in just one step. With the help of the amino group on chitosan, glucose oxidase is immobilized on nitrogen-doped carbon dots-modified carbon glassy electrodes by amino-carboxyl reactions. The nitrogen-induced charge delocalization at nitrogen-doped carbon dots can enhance the electrocatalytic activity toward the reduction of O2. The specific amino-carboxyl reaction provides strong and stable immobilization of GOx on electrodes. The developed biosensor responds efficiently to the presence of glucose in serum samples over the concentration range from 1 to 12 mM with a detection limit of 0.25 mM. This novel biosensor has good reproducibility and stability, and is highly selective for glucose determination under physiological conditions. These results indicate that N-doped quantum dots represent a novel candidate material for the construction of electrochemical biosensors.